Individual‐based simulations of genome evolution with ancestry: The GenomeAdmixR R package - Thijs Janzen; Fernando Diaz (Methods in Ecology and Evolution)
Abstract Hybridization between populations or species results in a mosaic of the two parental genomes. This and other types of genome admixture have received increasing attention for their implications in speciation, human evolution, Evolve and Resequence (E&R) and genetic mapping. However, a thorough understanding of how local ancestry changes after admixture and how selection affects patterns of local ancestry remains elusive. The complexity of these questions limits analytical treatment, but these scenarios are specifically suitable for simulation. Here, we present the R package GenomeAdmixR, which uses an individual‐based model to simulate genomic patterns following admixture forward in time. GenomeAdmixR provides user‐friendly functions to set up and analyse simulations under evolutionary scenarios with selection, linkage and migration. We show the flexible functionality of the GenomeAdmixR workflow by demonstrating (a) how to design an E&R simulation using GenomeAdmixR and (b) how to use GenomeAdmixR to verify analytical expectations following from the theory of junctions. GenomeAdmixR provides a mechanistic approach to explore expected genome responses to realistic admixture scenarios. With this package, we aim to aid researchers in testing specific hypotheses based on empirical findings involving admixing populations.